The Effect of Awareness Raising Technique towards Studentsâ Achievement and Reading Interest - Mahaputri, Dwi Settya (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
Reading is one of the primary subjects that should be mastered by the students in language learning. Yet, reading activity tends to be a boring activity. To increase the studentsâ interest, the lecturers should be able to stimulate the students awareness in reading. Therefore, this research is aimed to know the effect of Awareness Raising Technique in teaching reading toward students achievement and reading interest. This research was experimental research. The population was the second year students of English department of Education Abdi STKIP Payakumbuh. There were three classes. The sample was chosen by cluster sampling. The instruments of this research were reading test and questionnaire. To analyze the data, the researcher used the t-test and ANOVA formula 2x2. After analyzing the data the researcher found (1)students who were taught by using Awareness Raising Technique have better reading achievement than those who were taught by using Presentation Technique, (2) students with high reading interest have better reading achievement than those who were taught by using Presentation Technique, (3) students with high reading interest have better reading achievement than those who were taught by using Presentation Technique, and (4) there is no interaction between techniques and students reading interest toward students reading achievement at the second year English department of Education Abdi STKIP Payakumbuh.